2023
DOI: 10.3389/fpls.2023.1242469
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of cow dung and its biochar on Populus euphratica soil phosphorus effectiveness, bacterial community diversity and functional genes for phosphorus conversion

Yuxian Fan,
Guanghui Lv,
Yudong Chen
et al.

Abstract: IntroductionContinuous monoculture leading to soil nutrient depletion may cause a decline in plantation productivity. Cow dung is typically used as a cheap renewable resource to improve soil nutrient status. In this study, our purpose was to compare the effects of different cow dung return methods (direct return and carbonization return) on soil microbial communities and phosphorus availability in the root zone (rhizosphere soil and non-rhizosphere soil) of P.euphratica seedlings in forest gardens and to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…However, the increased mineralization of organic P in P. euphratica is linked to soil moisture, pH, and microorganism profiles, necessitating future research on foliar P fraction distribution. Based on the research conducted on the impact of cow dung and biochar on phosphorus efficiency in P. euphratica soil, bacterial communities, and functional genes (phoC, phoD, gcd, and pqqC; see [133] and references therein), the authors found that returning cow dung improves soil properties, seedling growth, and phosphorus availability, which are up-taken throughout the roots of P. euphratica. Biochar, a carbonized form of cow manure, has a more definite cumulative phosphorus content and promotion of bacterial diversity in arid regions.…”
Section: Effect Of Drought Stress On the Physiology Of P Euphraticamentioning
confidence: 99%
“…However, the increased mineralization of organic P in P. euphratica is linked to soil moisture, pH, and microorganism profiles, necessitating future research on foliar P fraction distribution. Based on the research conducted on the impact of cow dung and biochar on phosphorus efficiency in P. euphratica soil, bacterial communities, and functional genes (phoC, phoD, gcd, and pqqC; see [133] and references therein), the authors found that returning cow dung improves soil properties, seedling growth, and phosphorus availability, which are up-taken throughout the roots of P. euphratica. Biochar, a carbonized form of cow manure, has a more definite cumulative phosphorus content and promotion of bacterial diversity in arid regions.…”
Section: Effect Of Drought Stress On the Physiology Of P Euphraticamentioning
confidence: 99%